Study of Millimeter-Wave Rotational Spectra of Phosphorus Trifluoride in Ground,v2 = 1 and v4 = 1 States - Masoud Motamedi; Tahere Zohrevand (E-Journal of Chemistry)
The millimeter-wave rotational spectra of the ground and excited vibrational states v2 =1 and v4 =1 of the symmetric top molecule, PF3, have been analyzed again. The B0 = 7819.9907(13) MHz, DJ = 7.84984(41) kHz, DJk = -11.7644 (11) kHz, HJ = 15.678 (36) mHz, HJk = -66.46 (12) mHz and HkJ = 87.42 (15) mHz have been determined for ground state. The 1=±1 series have been assigned and the rotational parameters including B4 =7823.09212(41) MHz, (q+t)4 = -29.49200(65) MHz, rt=2.9465 (13) MHz and (Cζ)4 = -3010.94684(41) MHz for v4 =1 state were determined accurately